Transforming Medicine with Nanobiotechnology: Nanocarriers and Their Biomedical Applications - Arun Karnwal; Vikas Sharma; Gaurav Kumar; Amar Yasser Jassim; Aradhana Dohroo; Iyyakkannu Sivanesan (Pharmaceutics)
Nanobiotechnology, at the intersection of nanotechnology and biology, represents a burgeoning field poised to revolutionize medicine through the use of advanced nanocarriers. These nanocarriers, endowed with distinctive physiobiological attributes, are instrumental in diverse therapeutic domains including drug delivery for microbial infections, cancer treatment, tissue engineering, immunotherapy, and gene therapy. Despite the transformative potential, several challenges hinder their efficacy, such as limited drug capacity, suboptimal targeting, and poor solubility. This review delves into the latest advancements in nanocarrier technologies, examining their properties, associated limitations, and the innovative solutions developed to address these issues. It highlights promising nanocarrier systems like nanocomposites, micelles, hydrogels, microneedles, and artificial cells that employ advanced conjugation techniques, sustained and stimulus-responsive release mechanisms, and enhanced solubility. By exploring these novel structures and their contributions to overcoming existing barriers, the article emphasizes the vital role of interdisciplinary research in advancing nanobiotechnology. This field offers unparalleled opportunities for precise and effective therapeutic delivery, underscoring its potential to reshape healthcare through personalized, targeted treatments and improved drug performance.